Association of lipoprotein(a) with left ventricular hypertrophy assessed by electrocardiogram in adults: a large cross-sectional study - Yan, Xuejiao; Gong, Jing; Wang, Zhenwei; Wang, Fangfang; Qi, Chunjian (Frontiers in Endocrinology, 2023)
Background and aims Increasing evidence supports a causal relationship between lipoprotein(a) [Lp(a)] and atherosclerotic cardiovascular disease, yet its association with left ventricular hypertrophy (LVH) assessed by electrocardiogram (ECG) remains unknown. The aim of this study was to explore the relationship between Lp(a) and LVH assessed by ECG in general population. Methods and results In this cross-sectional study, we screened 4,052 adults from the participants of the third National Health and Nutrition Examination Survey for analysis. Lp(a) was regarded as an exposure variable. LVH defined by the left ventricular mass index estimated from ECG was considered as an outcome variable. Multivariate logistic regression and restricted cubic spline (RCS) were used to assess the relationship between Lp(a) and LVH. Individuals with LVH had higher Lp(a) compared to individuals without LVH (P< 0.001). In the fully adjusted model, Lp(a) was strongly associated with LVH when as a continuous variable (per 1-unit increment, OR: 1.366, 95% CI: 1.043-1.789, P = 0.024), and higher Lp(a) remained independently associated with a higher risk of LVH when participants were divided into four groups according to quartiles of Lp(a) (Q4 vs Q1, OR: 1.508, 95% CI: 1.185-1.918, P = 0.001). And in subgroup analysis, this association remained significant among participants< 60 years, ≥ 60 years, male, with body mass index< 30 kg/m2, with hypertension and without diabetes (P< 0.05). In addition, we did not observe a nonlinear and threshold effect of Lp(a) with LVH in the RCS analysis (P for nonlinearity = 0.113). Conclusion Lp(a) was closely associated with LVH assessed by ECG in general population.